RPM MEASUREMENT COMPARISON USING A THERMOMETER AND LM393 MICROCONTROLLER - Nanda, Rizki Aulia; Karyadi, Karyadi; Roban, Roban; Dewadi, Fathan Mubina (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2024)
RPM measurement is a crucial measurement tool for assessing a machine's rotation quality and ensuring that it meets the DC motor manufacturer's specifications. The quality of rotation of electric motors and combustion motors can both be observed through RPM measurements. The precision with which the LM393 sensor measures the rotation of a DC motor engine is the problem formulation in this study. Thus, the purpose of this study is to evaluate the rotation measurement accuracy of the LM393 Microcontroller sensor and compare it to a traditional tachometer. In order to conduct rotational variations on the DC motor, the following voltages will be applied: 0.93V, 2.83V, 4.25V, 7.05V, and 9.07V. Next, a tachometer and an LM393 microcontroller are used to measure the DC motor rotation. The gathered data will be made available for verification. Based on the measurement results, the corresponding data differences are -5.560 RPM, -1.577 RPM, -2.182 RPM, -3 RPM, and 0.334 RPM. Therefore, measurement validation was done based on the disparity in readings, yielding results of 0.252%, -1.45%, 0.12%, 0.038%, and 0.0725%. Based on validation results showing a presentation of no more than 10%, the LM393 measuring tool for DC motor RPM measurement is deemed valid and suitable for use.